El control interno y la toma de decisiones en la Gerencia Regional de Desarrollo Agrario y Riego de Loreto, 2023 - Melendez Ruiz, Salvith Luisa (2025)
The objective of the research was to determine the relationship between internal control and decision making in the Regional Management of Agrarian Development and Irrigation of Loreto, 2023; where a descriptive correlational level method and a non-experimental design were used, the sample was 50 administrative workers to whom an instrument was used for data collection. According to the results obtained, internal control was rated as regular (36%), this is because the organizational structure generally facilitates the achievement of objectives, although it only occasionally considers the risk of fraud and develops adequate control activities. However, reliable information is almost always available and is adequately supervised to ensure compliance with established procedures. Regarding decision making, it is rated as adequate (40%), since management almost always clearly identifies problems and objectively evaluates alternative solutions. However, it only occasionally systematically analyzes data and considers different perspectives when developing solutions. Finally, a moderate positive correlation is established between internal control and decision making, contrasted by a coefficient of 0.613 and a statistical significance of 0.000.